+0  
 
0
58
1
avatar+262 

(x-1)(x+2)=70

 

(6x^2-7x)^2-2(6x^2-7x)-3=0

 

9(x-1)^2=4(x-2)^2

ISmellGood  Sep 26, 2017
Sort: 

1+0 Answers

 #1
avatar+4790 
+2

(x - 1)(x + 2)  =  70

                                      Multiply out the left side of the equation.

x2 + x - 2  =  70

                                      Subtract  70  from both sides of the equation.

x2 + x - 72  =  0

 

Can you think of two numbers add to  1  and multiply to  -72?   →   -8  and  +9 .

So the left side can be factored like this...

 

(x - 8)(x + 9)  =  0           Now we set each factor equal to zero and solve for  x  .

 

x - 8  =  0      or      x + 9  =  0

     x  =  8      or            x  =  -9

 

-------------------

 

I don't know the best way to do the second one, but I'm sure someone else on here does.

Here's the third one:

 

9(x - 1)2  =  4(x - 2)2     Take the ± square root of both sides.

                                     (We only need to write the ± on one side though.)

 

\(\sqrt{9(x-1)^2}\,=\,\pm\sqrt{4(x-2)^2} \\~\\ \sqrt9\cdot\sqrt{(x-1)^2}\,=\,\pm\sqrt4\cdot\sqrt{(x-2)^2} \\~\\ 3(x-1)\,=\,\pm2(x-2) \)

 

\(3x-3\,=\,\pm(2x-4)\)       Split this into two seperate equations.

 

\(\begin{array} \ 3x-3=+(2x-4)\qquad\text{or}\qquad&3x-3=-(2x-4) \\~\\ 3x-3=2x-4&3x-3=-2x+4 \\~\\ x-3=-4&5x-3=4 \\~\\ x=-1&5x=7 \\~\\ &x=\frac75 \end{array}\)

hectictar  Sep 27, 2017

26 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details